Fabrication and simulation studies on sound absorption coefficient of natural microfibers reinforced silicone rubber - Afira Ainur Rosidah; Vuri Ayu Setyowati (University of Muhammadiyah Jakarta, 2022)
Silicone rubber (SR) is known as stable and able to get through an extreme environment. Moreover, the combination of SR and natural fiber as the composite for the sound absorption application is still limited. For this reason, this study was aimed to fabricate the natural fiber-reinforced porous SR for the sound absorption material. Then, the composites were simulated using multilinear regression method to predict the sound absorption coefficient and its factor influence. The composite fabrication was started with the alkalization of oil palm fiber treatment. Furthermore, the porous SR were prepared using NaCl filler to form the pores. Then, the specimen containing NaCl was soaked in warm water and all specimens were dried at 110 °C to remove the remaining water. The addition of fibers enhances the density value to the highest value of 1.061 g/cm3 with 6 wt% microfibers. The higher the microfiber addition led to the higher α value in low frequency, it occurred at SR/6 wt% microfibers with the α value of 0.356. Additionally, the most suitable equation with the smallest error is Equation 6 which has the RMSE and values of 0.05234 and 0.6138, respectively.